Sustainability reporting indicators used by oil and gas companies in GCC countries: IPIECA guidance approach - Aljanadi, Yaseen; Alazzani, Abdulsamad (Frontiers in Environmental Science, 2023)
he purpose of this article is to assess the quality of the sustainability reporting indicators used by oil and gas companies (OGCs) in Gulf Cooperation Council (GCC) countries. This study utilizes the International Petroleum Industry Environmental Conservation Association (IPIECA) guidance as a new robust methodology to assess the quality of sustainability reporting, which is considered a comprehensive benchmark that directly relates to the oil and gas sector. This study conducts a content analysis of the sustainability reports published by OGCs in GCC countries for the 2016–2018 period. The results reveal that the quality of the sustainability indicators disclosed by companies is largely unsuitable. The results also show that companies fail to report detailed information on environmental indicators as the most important category for OGCs. The findings demonstrate that most OGCs in Qatar pay more attention to sustainable reporting indicators than the OGCs in other GCC countries. This study successfully addresses many previously outstanding issues regarding the quality of the sustainability reporting indicators used by OGCs in GCC countries. Hence, the findings paint a clear picture of the situation so that regulators, policymakers, and managers can correct the existing shortcomings in the quality of sustainability reporting and promote sustainability reporting guidance best practices.